2021
DOI: 10.3390/jcm10020281
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis as an Open Window to Systemic Inflammatory Diseases

Abstract: Spondyloarthritis (Spa), Behçet’s disease (BD) and sarcoidosis are major systemic inflammatory diseases worldwide. They are all multisystem pathologies and share a possible ocular involvement, especially uveitis. We hereby describe selected cases who were referred by ophthalmologists to our internal medicine department for unexplained uveitis. Physical examination and/or the use of laboratory and imaging investigations allowed to make a diagnosis of a systemic inflammatory disease in a large proportion of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 188 publications
(262 reference statements)
0
8
1
1
Order By: Relevance
“…Despite the common diagnosis of sarcoidosis, followed by HLA-B27-associated uveitis and then Behcet's disease (BD) (33,34), our study found BD to be the most common diagnosis, followed by ankylosing spondylitis (AS) and systemic lupus erythematosus (SLE). This divergence might be due to the high prevalence of BD reported in Syria, a silk road country (35), or it could re ect racial differences and sample size variation.…”
Section: Discussionmentioning
confidence: 58%
“…Despite the common diagnosis of sarcoidosis, followed by HLA-B27-associated uveitis and then Behcet's disease (BD) (33,34), our study found BD to be the most common diagnosis, followed by ankylosing spondylitis (AS) and systemic lupus erythematosus (SLE). This divergence might be due to the high prevalence of BD reported in Syria, a silk road country (35), or it could re ect racial differences and sample size variation.…”
Section: Discussionmentioning
confidence: 58%
“…En relación con el tratamiento, los medicamentos de elección al momento del diagnóstico fueron los medicamentos tópicos como esteroides, AINE tópicos, anticolinérgicos e inhibidores de la anhidrasa carbónica. Los esteroides sistémicos e inmunosupresores se dieron en un número más pequeño de pacientes, lo que habla de menos compromiso sistémico y casos severos 29 .…”
Section: Discussionunclassified
“…About 80 causes of uveitis have been described and these can be classified into four main groups. In Western countries, approximately one-quarter of cases are linked to ophthalmologic diseases, one-quarter to systemic diseases fulfilling consensual diagnostic criteria, one-quarter to presumed systemic diseases, and one-quarter have an unexplained origin [ 5 ]. Uveitis of unexplained origin, also known as idiopathic uveitis, represents 23–44% of cases according to recent studies [ 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%